2021
DOI: 10.1186/s12866-021-02125-1
|View full text |Cite
|
Sign up to set email alerts
|

Dysbiosis of gut microbiota and its correlation with dysregulation of cytokines in psoriasis patients

Abstract: Background Psoriasis is an inflammatory skin disease associated with multiple comorbidities and substantially diminishes patients’ quality of life. The gut microbiome has become a hot topic in psoriasis as it has been shown to affect both allergy and autoimmunity diseases in recent studies. Our objective was to identify differences in the fecal microbial composition of patients with psoriasis compared with healthy individuals to unravel the microbiota profiling in this autoimmune disease. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 43 publications
2
69
0
Order By: Relevance
“…It has been reported that, compared with healthy patients, the abundance of Prevotella in the intestines of patients with psoriasis is increased, while that of the Porphyromonadaceae family, to which Parabacteroides distasonis belongs, is decreased (32,33). Thus, our ndings suggest that the intestinal microbiota plays an important role in the progression of psoriasis.…”
Section: Discussionsupporting
confidence: 52%
“…It has been reported that, compared with healthy patients, the abundance of Prevotella in the intestines of patients with psoriasis is increased, while that of the Porphyromonadaceae family, to which Parabacteroides distasonis belongs, is decreased (32,33). Thus, our ndings suggest that the intestinal microbiota plays an important role in the progression of psoriasis.…”
Section: Discussionsupporting
confidence: 52%
“…Later, we found the recovery process of patients with psoriasis was accompanied by reduction of certain "psoriatic characteristic bacterial genera" (13,15,16,33), which had been identified by published studies comparing gut bacteria in patients with psoriasis and healthy controls. Specific bacterial differences at all levels of taxonomic classification were summarized in Supplementary Table 9 (13)(14)(15)(16)(17)(18)(33)(34)(35)(36)(37)(38)(39). The F/B ratio has been shown to be significantly related to certain psoriasis comorbidities (e.g., metabolic syndrome) and be positively correlated with PASI score by comparison of gut metagenome between patients with psoriasis and healthy people (15,37).…”
Section: Discussionmentioning
confidence: 99%
“…Microbiota produce short and medium chain fatty acids which can regulate immune responses, which may explain their link to psoriasis pathogenesis [ 204 ]. For example, alterations in the gut microbiome correlate with increases in inflammatory markers, including the IL-2 receptor and the complement 3 protein [ 205 ]. Additionally, the gut microbiome from psoriasis patients has a lower gene expression of proteins which synthesise butyrate (an anti-inflammatory short-chain fatty acid) than healthy controls [ 206 , 207 ].…”
Section: Contributors To Barrier Dysregulation In Psoriasismentioning
confidence: 99%